"It just took the pressure off": The voices of Veterans' family caregivers in a participant-directed program. Issue 3 (1st October 2016) - Milliken, Aimee; Mahoney, Ellen K.; Mahoney, Kevin J.
ABSTRACT: The Veteran-Directed Home and Community Based Services Program (VD-HCBS) operates using a participant-direction approach, allowing Veterans to self-direct services. Only a small body of literature has explored the impact of these programs on caregivers. This study aimed to explore the experiences of caregivers in VD-HCBS. Telephone focus groups and interviews were conducted with caregivers ( n  = 23; 52.2% spouses; 8.7% male). Conventional content analysis revealed five categories: Coming home and staying home; Taking the pressure off; Providing security; Giving us time as a couple; and Importance of choice. Stories highlighted sources of stress and mechanisms behind stress relief and support.